Genotyping and DNA microarray based characterization of Staphylococcus aureus isolates from rabbit carcasses. (February 2016) - Merz, Axel; Stephan, Roger; Johler, Sophia
Abstract: Staphylococcus aureus can cause staphylococcal food poisoning. Although the organism is frequently detected on rabbit carcasses, little is known about the characteristics of S. aureus strains contaminating rabbit meat. In this study, 137 S. aureus isolates originating from 137 rabbit carcasses were spa typed and characterized by DNA microarray. The isolates were assigned to CC5, CC7, CC8, CC15, CC96, CC101, CC121, and ST890, and to 13 spa types (t056, t085, t091, t160, t179, t681, t741, t745, t1190, t1773, t4770, t8456, t14871). Enterotoxin genes detected included sea, sed, sej, and ser. In addition, the egc operon, encoding the newly described staphylococcal enterotoxins SEG/SEI/SElM/SElN/SElO/SElU, was found in all isolates except those of t091. While none of the examined isolates presented genes conferring methicillin, vancomycin, or aminoglycoside resistance, we frequently detected blaZ / I / R conferring resistance to penicillin. The isolates represented a heterogeneous group assigned to clonal lineages detected among humans and animals, with two spa types exclusively associated with rabbit meat (t4770, t8456). Highlights: S. aureus isolates from rabbit carcasses represent a heterogeneous group. Two of the 13 detected spa types are exclusively associated with rabbit meat. S. aureus isolates from rabbit carcasses exhibit a wide range of enterotoxin genes. The most frequently detected enterotoxin genes belonged to the egc cluster.